2001
DOI: 10.1192/bjp.179.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the incidence of schizophrenia in rural Dumfries and Galloway and urban Camberwell

Abstract: The incidence of schizophrenia in urban Camberwell was higher than that in rural Dumfries and Galloway; the high incidence of non-Whites in Camberwell largely explains the urban/rural difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 24 publications
5
60
1
1
Order By: Relevance
“…Key details of the included studies are shown in Tables S1–S4, which can be found in Additional File 4. The systematic review identified 100 core studies [13,31,33,40,41,45-61,63,65-127,148,180-192]. The 158 included studies were drawn from 32 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Key details of the included studies are shown in Tables S1–S4, which can be found in Additional File 4. The systematic review identified 100 core studies [13,31,33,40,41,45-61,63,65-127,148,180-192]. The 158 included studies were drawn from 32 countries.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first nationwide assessment of the potential selective migration of persons with schizophrenia towards urban areas as a consequence of the disorder or its prodromata. In addition, this study has important relevance for the interpretation of retrospective studies, which may have the advantage of using systematic diagnostic criteria (Allardyce et al, 2001;Kirkbride et al, 2006) as opposed to the clinical diagnoses used by most prospective studies. Despite methodological differences in study designs and evidence of urban-rural drift around disease onset, the urban-rural differences in the prevalence of the schizophrenia is nearly identical to the urban-rural differences in the incidence rate ratio of schizophrenia.…”
Section: Discussionmentioning
confidence: 98%
“…The retrospective studies have typically been based on surveys of populations; they have relied on structured interviews of the participants, and have measured urbanization at time of the interview, i.e., after disease onset (e.g. (Allardyce et al, 2001;Faris and Dunham, 1939;Jarvis, 1855;Scully et al, 2004;Takei et al, 1992;Takei et al, 1995;Torrey et al, 1997;Torrey and Bowler, 1990; van Os et al, 2001;Waddington et al, 1997;White, 1903;Youssef et al, 1991;Youssef et al, 1999)). …”
Section: Discussionmentioning
confidence: 99%
“…Explanations for this association include differences in individual characteristics (eg, different levels of migration or family history), familial characteristics, selective migration, exposure to infections, exposure to pollutants, diet, and the social environment. [21][22][23][24] Evidence from a Danish sibling design suggest that the causes responsible for these urban-rural differences are related to family-level factors although the influence of individual-level factors could not be ruled out. 21 Neighbourhood effect, social fragmentation and deprivation, and other differences between life in cities and rural areas have been found to explain better the association of urbanicity with psychosis than individual differences.…”
Section: Discussionmentioning
confidence: 99%